ANALISIS EFEKTIVITAS MESIN CNC PLATE CUTTING PADA PT. SUMBARTEC JAYA LIEVINDO - Amelia, Yohana; Ganda Sirait (LPPM Universitas Putera Batam, 2024)
PT.Sumbartec jaya lievindo located in Batam, Indonesia, is a leading company in the manufacturing and technology sector. The problem that occurs in this study is that manual and automatic (CNC) cutting machines cause several defects in the plate, such as non-diagonal cutting and uneven edges, which result in defective products and interfere with the effectiveness of the production process. The purpose of this study is to measure machine performance using the OEE (overall equipment effectiveness) approach so that recommendations can be given to improve machine effectiveness by applying causal analysis (fishbone). The method used in this research is Overall Equipment Effectiveness (OEE) as a tool to measure overall equipment performance. Based on the results of the study, it is found that the average availability value is 83%, for the average performance value, the value is 87%, while the average rate of quality product is 93%, and the average value (OEE) is 67% Thus, the average OEE value is still below the World OEE Class standard which is worth 85%. The types of six big losses that dominantly cause low OEE values on cnc plate cutting machines are reduced speed losses and equipment failure losses have the same value as Idling & minor stoppages. Idling & minor stoppages 17% is the biggest losses of all losses that occur and equipment failure losses are in second place with a value of 16.%.